Clinical Profile of Drooling in Cerebral Palsy Patients at Physical Medicine and Rehabilitation Department Dr. Soetomo General Hospital Surabaya Period January 1st, 2016 – December 31st, 2017 - Baiq Dwi Hadiatul Azmi; Noor Idha Handajani; I Gusti Made Reza Gunadi Ranuh (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Cerebral palsy (CP) is a non-progressive neurological motor disorder. The incidence of CP in developed countries is around 2 to 2.5/1,000 births. Drooling is a condition when the saliva comes out of the mouth uncontrollably. The number of drooling cases can be estimated to be 10-37% in children with CP. This study aimed to examine and analyze the clinical profile of drooling in CP patients who visited Physical Medicine and Rehabilitation Department Dr. Soetomo General Hospital Surabaya period January 1st, 2016 - December 31st, 2017 according to their ages, gender, CP types, swallowing disorders, speech disorders, and nutritional status.Methods: This study used a retrospective analytical method, and used the patients' medical record data at Physical Medicine and Rehabilitation Department Dr. Soetomo General Hospital Surabaya period January 1st, 2016 - December 31st, 2017.Results: There were 45 subjects consisted of 23 men and 22 women. The peak incidence occurred in the 1-5 years age range. Whereas the most type of CP were quadriplegic spastic. There were 7 patients (15.6%) who suffered swallowing disorders, while speech disorders dominated the pattern of symptoms in the sample (95.6%). A total of 21 people or 52.5% of patients with CP and having clinical manifestations of drooling had good nutritional status. Conclusion: In this study, we can conclude that peak incidence of CP was mostly in the 1-5 years old range, and quadriplegic spastic was the most popular types of CP. Speech disorders dominated the pattern of symptoms.